Individual-level social capital and COVID-19 vaccine hesitancy in Japan: a cross-sectional study. Issue 5 (30th November 2022) - Machida, Masaki; Kikuchi, Hiroyuki; Kojima, Takako; Nakamura, Itaru; Saito, Reiko; Nakaya, Tomoki; Hanibuchi, Tomoya; Takamiya, Tomoko; Odagiri, Yuko; Fukushima, Noritoshi; Amagasa, Shiho; Watanabe, Hidehiro; et al.
ABSTRACT: To reduce vaccine hesitancy, it is important to identify factors that can intervene at the individual or community level. Social capital is a possible factor because it is associated with various vaccine hesitancy, such as for measles and influenza. However, limited studies have explored the association between social capital and vaccination for COVID-19, which is an unprecedented pandemic and infodemic. Therefore, this study aimed to clarify the association between social capital and COVID-19 vaccination during the pandemic. This cross-sectional study used quota sampling for an online-based survey. Participants were asked whether they had previously been vaccinated for COVID-19 and their intention to receive a COVID-19 vaccine booster. Social capital was evaluated using three measures (individual-level civic participation, social cohesion, and reciprocity). Multiple logistic regression analysis was performed to clarify the association between social capital and previous COVID-19 vaccination status as well as intention to receive a COVID-19 booster. Participants were 2, 313 individuals, of whom 87.2% had received a COVID-19 vaccine; 72.3% intended to obtain a COVID-19 booster. Individuals with any social capital are more likely to receive a COVID-19 vaccination than those with none (OR: 1.73, 95%CI: 1.18–2.54; OR: 1.58, 95%CI: 1.22–2.05; OR: 3.05, 95%CI: 2.15–4.33). These indicators were also associated with the intention to receive a COVID-19 booster. Thus, our results suggest that among the general public, those with individual-level social capital are more likely to receive a COVID-19 vaccination than those with none. Social capital may be a factor that can reduce vaccine hesitancy during a pandemic.